If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y = 7y + 24 Reorder the terms: 9y = 24 + 7y Solving 9y = 24 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 9y + -7y = 24 + 7y + -7y Combine like terms: 9y + -7y = 2y 2y = 24 + 7y + -7y Combine like terms: 7y + -7y = 0 2y = 24 + 0 2y = 24 Divide each side by '2'. y = 12 Simplifying y = 12
| 5+4t=7(t) | | -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 | | 3x+60=10x+11 | | 23=-7(6v+7)+5(1-5v) | | 1.9/250=x/650 |